Intellectuals incorporated : politics, art, and ideas inside Henry Luce's media empire - Vanderlan, Robert (Politics and culture in modern America., 2010)
Publishing tycoon Henry Luce famously championed many conservative causes, and his views as a capitalist and cold warrior were reflected in his glossy publications. Republican Luce aimed squarely for the Middle American masses, yet his magazines attracted intellectually and politically ambitious minds who were moved by the democratic aspirations of the New Deal and the left. Much of the best work of intellectuals such as James Agee, Archibald MacLeish, Daniel Bell, John Hersey, and Walker Evans owes a great debt to their experiences writing for Luce and his publications.